2015
DOI: 10.1186/s13054-015-0874-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effectiveness of a sedation protocol minimizing benzodiazepine infusions and favoring early dexmedetomidine: a before-after study

Abstract: IntroductionRandomized controlled trials suggest clinical outcomes may be improved with dexmedetomidine as compared with benzodiazepines; however, further study and validation are needed. The objective of this study was to determine the clinical effectiveness of a sedation protocol minimizing benzodiazepine use in favor of early dexmedetomidine.MethodsWe conducted a before-after study including adult surgical and medical intensive care unit (ICU) patients requiring mechanical ventilation and continuous sedatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 23 publications
1
16
0
1
Order By: Relevance
“…This may be due in part to the staffing practices in the medical ICUs and the history of efforts directly aimed at optimizing the care of ventilated subjects in those units. 6,[8][9][10] However, we cannot be certain that our findings would be the same in ICUs having different staffing models and protocols for the prevention of events such as VAEs and VAP. Our study data were also derived from a single center, which limits the generalizability of our findings.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…This may be due in part to the staffing practices in the medical ICUs and the history of efforts directly aimed at optimizing the care of ventilated subjects in those units. 6,[8][9][10] However, we cannot be certain that our findings would be the same in ICUs having different staffing models and protocols for the prevention of events such as VAEs and VAP. Our study data were also derived from a single center, which limits the generalizability of our findings.…”
Section: Discussionmentioning
confidence: 70%
“…6,7 Moreover, the medical ICUs have a long history of routinely using protocols for the weaning of mechanical ventilation, sedation management, and prevention of VAP and VAEs developed in conjunction with the infection prevention department and the Barnes-Jewish Hospital Departments of Respiratory Care and Nursing. 6,[8][9][10] We also recorded the exact number of endotracheal tube cuff pressure assessments performed in both groups.…”
Section: Study Outcomes/objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Cada animal recebeu aproximadamente 500mL de propofol em 24 horas, e possivelmente o curto tempo para extubação e o moderado tempo para recuperação ocorreram devido ao baixo efeito cumulativo do propofol (Luiz et al, 2013). Em UTI humana, a associação de propofol e midazolam é normalmente utilizada, entretanto altas doses de benzodiazepínicos têm sido associadas com aumento do tempo de recuperação e desmame da VM (Skrupky et al, 2015). Vieira et al (2013) também não observaram diferenças no tempo para extubação, deambulação e recuperação total em cães submetidos à infusão de propofol e propofol/cetamina em taxas variadas durante 60 minutos, porém esses tempos aumentam consideravelmente em infusões para procedimentos de OSH, devido à necessidade de maiores doses para a manutenção dos planos.…”
Section: Resultsunclassified
“…decreased sedation, decreased duration of mechanical ventilation, etc.) but have had either no effect on delirium incidence [31,32] or strangely in one study of a protocol minimizing benzodiazepines in favor of dexmedetomidine-an increase in delirium prevalence (81 vs. 93 %, p = 0.013) [33]. A systematic review on ICU delirium bundles concluded that creating an integrated management protocol with a higher number of individual elements (at least six different prevention strategies), such as the PAD or ABCDE bundles, may improve clinical outcomes such as mortality and hospital length of stay, but did not appear to be associated with decreased incidence of delirium [34].…”
Section: Preventionmentioning
confidence: 99%